An examination of difficulties accessing surgical care in Canada from 2005-2014: Results from the Canadian Community Health Survey - Sommer, Jordana Liyat (PLoS One, 2020)
BACKGROUND: Difficulties accessing surgical care (e.g., related to wait times, cancellations, cost, receiving a diagnosis) are understudied in Canada. Using population-based data, we studied difficulty accessing non-emergency surgical care, including (1) the incidence and annual changes in incidence, (2) types of difficulties, and (3) associated factors (e.g., sociodemographics, surgery characteristics). METHODS: Cross-sectional data from the Canadian Community Health Survey annual components were analyzed from 2005–2014. Weighted frequencies established the annual incidence of difficulty accessing surgical care, and total incidence of types of difficulties. Chi-square analyses, independent samples t-tests, and a multivariable logistic regression examined sociodemographic and surgery-related characteristics associated with difficulty accessing surgical care. RESULTS: Among individuals who required past-year non-emergency surgery between 2005–2014 (weighted n = 3,052,072), 15.6% experienced difficulty accessing surgical care. The most common difficulty was “waited too long for surgery” (58.5%). There were significant differences in the incidence of difficulty according to year (Χ(2) = 83.50, p < .001) from 2005–2014. The incidence of difficulty accessing surgery varied according to sex (Χ(2) = 4.02, p < .05), surgery type (Χ(2) = 96.09, p < .001), party responsible for cancellation/postponement (Χ(2) range: 4.36–19.01, p < .05), and waiting time (t = 10.59, p < .001). In particular, males, orthopedic surgery, and surgery cancelled by the surgeon or hospital had the highest rates of difficulty. CONCLUSION: Results provide insight into the difficulties experienced by patients accessing elective surgery, and the associated factors. These results may inform targeted healthcare interventions and resource reallocation to reduce these occurrences.